Pengaruh Penerapan E-filing, Pemahamn Peraturan Perpajakan dan Sanksi Pajak Terhadap Tingkat Kepatuhan Wajib Pajab Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Serpong - Selly Putri Lestari; Suparmin Suparmin (JURNAL PUNDI, 2023)
ABSTRACTThis study aims to determine the effect of the application of e-filing, understanding of tax regulations and tax sanctions on the level of compliance of individual taxpayers at the Serpong Pratama Tax Service Office, Tangerang. The type of research used in this study is quantitative research. The source of data used in this study is primary data. The population in this study is individual taxpayers registered at KPP Pratama Serpong, Tangerang. Determination of samples in this study using the simple randome sampling method and obtained data from 130 respondents. Analysis techniques use analysis, namely, validity tests, reliability tests, then classical assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests and multiple linear regression tests. Hypothesis testing uses the coefficient of determination test, F test, and t test. Data analysis using the help of SPSS software version 26. The results of this study show that the application of e-filing, understanding of tax regulations and tax sanctions simultaneously affect taxpayer compliance. Based on the results of the study, the application of e-filing and understanding of tax regulations partially affects taxpayer compliance, while tax sanctions partially do not affect taxpayer compliance.Keywords: Application of E-filing, Understanding of Tax Regulations, Tax Sanctions and Taxpayer Compliance.